Findings from colposcopy and colposcopy directed biopsy in cervical precancerous lesions - Bhattacharjee, Sulekha; Begum, Khadiza; Waddader, Priyanka; Biswas, Supran (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Pap smear test has been less successful in identifying those women with the highest risk for pre-malignant disease, so the patients with equivocal Pap smear would need further evaluation with colposcopy. Performing the colposcopy with more accuracy would result in better prognosis of pre-malignant lesions. However, performing a comparison with directed biopsy is required to obtain more definite results. The aim of this study was to determine colcoscopic findings in VIA positive cases. Methods: This observational study was conducted at the Department of Gynaecology and Obstetrics in Chittagong Medical College Hospital, Chittagong from September 2014 to February 2015. A total 72 women of VIA positive cases attended at colposcopy clinic of CMCH were included in this study. These patients were selected nonrandomly according to inclusion criteria. All patients were sign a written informed consent before recruitment into the study. According to colposcopy diagnosis was done by Reid colposcopic index. All patients were undergone directed biopsy followed by histopathology. Data were collected under guidance and advice of the supervisor through a structured questionnaire. Results: Almost two-thirds of the cases were 30-39 years age group. Among the 72 cases the presentations were mainly excessive vaginal discharge 61.1%, dyspareunia 16.7%, post-coital bleeding 9.7% and abnormal inter-menstrual bleeding 12.5%. Colposcopically 90.3% had CIN and invasive lesions, while 9.7% was normal. Colposcopically directed punch biopsy revealed in 84.7% cases positive lesions and 15.3% had not any CIN or invasive lesions. Conclusions: This study demonstrated high accuracy. Sensitivity is lower in our studies, probably because biopsies were performed in all cases